Analisis Minat Belajar Siswa melalui Pendekatan Matematika Realistik pada Pembelajaran Berbasis Daring di Kelas VI Sekolah SDN Blendung - Unaenah, Een; Saharani, Aura Luthfia; Putri, Chika Meiliana; Pertiwi, Nabila Putri (YASIN, 2023)
This study aims to analyze students' interest in learning through a realistic mathematics approach. This approach emphasizes the use of mathematics in real-life situations to enhance student engagement and understanding. This analysis aims to assess the level of interest and enthusiasm of students in learning mathematics through this method. The research method used is class observation, interviews, surveys and evaluation of student performance. Data was collected by observing students' involvement in learning, students' responses to assignments and challenges, in everyday life. students show high interest and enthusiasm in learning realistic mathematics. They actively participate in discussions, collaborate with classmates and ask questions. Students also show a positive attitude towards mistakes and challenges, experiment, think creatively, and see mistakes as opportunities to learn. In addition, students are able to understand mathematical concepts and relate them to real life. They see the relevance and benefits of learning mathematics in everyday life. Feedback and assessment provide additional motivation for students to continue learning and increase understanding. The results of the study concluded that a realistic mathematics approach can be effective in increasing students' interest in learning. By adopting this approach, students participate actively, see the relevance of mathematics to their lives, and develop a positive attitude towards mistakes and challenges. The implication of this research is the importance of using relevant and situational approaches in learning mathematics to increase students' learning interest.